The Influence of Foreign Investors, Government Policy, Economic and Political Conditions on the Growth of the Indonesian Capital Market - Pratama, Angga (Yayasan Gema Bina Nusantara, 2024)
This research aims to explore the impact of foreign investors, government policies, and economic and political conditions on the growth of the Indonesian capital market. The data used is secondary data obtained from official sources such as government agency websites and official publications. Researchers conducted the analysis using the multiple linear regression method, testing classical assumptions prior to its implementation. The research results show that foreign investors and government policies do not significantly influence the growth of the Indonesian capital market. Economic factors, such as economic growth, inflation, and interest rates, have a greater influence on capital market performance. Apart from that, political conditions also play an important role, where political stability and consistent government policies can create a positive investment climate. Overall, these factors together influence the growth of the capital market in Indonesia, showing the complexity of capital market analysis that requires a holistic approach.